The CATEGORY SHIFT OF NOUN CLAUSE IN CITY OF FALLEN ANGELS NOVEL AND ITS TRANSLATION - Yuliana, Tiarma Ika; Oktavita, Rr. Astri Indriana; Ghufron, Muhammad Ali; Ulfa, Rima Novia (Pujangga : Jurnal Bahasa dan Sastra, 2023)
Every language has its own grammatical system, and this makes shift when translating cannot be avoided. Catford (1965) introduces two kinds of shifts in translation: level shifts and category shifts. He further explains that there are four categories in category shift, including structure shift, class shift, unit shift and intra-system shift. The aim of this article to analyze the translation shift in the novel “City of Fallen Angels” by Cassandra Clare and its Indonesian by Meda Satria. The writers focus on the category shifts in noun clause that be found in the novel “City of Fallen Angels” by Cassandra Clare and its translation. The data were analyzed by applying the qualitative descriptive method. The result shows that there are 134 data, it can be classified as follows : 57 data of unit shift (42%), 44 data of structure shift (33%), 19 data of class shift (14%), and 14 data of intra-system shift (11%)..